Ukrajinska Avangarda 1910-1930. (Zagreb : Muzej Suvremene Umjetnosti, 1990)
Bogomazov, Oleksandr ; Ekster, Aleksandra ; Genke-Meller, Nina ; Ivanov, Ivan ; Kavaleridze, Ivan ; Kosarjev, Boris ; Meller, Vadim ; Nikritin, Solomon ; Paljmov, Viktor ; Petrickij, Anatolj ; Piskorskij, Konstjantin ; etc.
Ukrajinska Avangarda 1910-1930, Muzej Suvremene Umjetnosti, Zagreb, 16.12.1990 - 24.2.1991
Kroatisch & Engels
kunstcatalogus
Keywords: Oekraïne